Geriatric symptoms associated with healthy life expectancy in older people in Japan - Rikuya Hosokawa; Toshiyuki Ojima; Tomoya Myojin; Katsunori Kondo; Naoki Kondo (Komiyama Printing Co. Ltd, 2023)
Background: We investigated the relationship between characteristic geriatric symptoms and healthy life expectancy in older adults in Japan. Additionally, we determined relationship predictors that would help formulate effective approaches toward promoting healthy life expectancy. Methods: The Kihon Checklist was used to identify older people at high risk of requiring nursing care in the near future. We evaluated the association of geriatric symptoms with healthy life expectancy while considering risk factors (frailty, poor motor function, poor nutrition, poor oral function, confinement, poor cognitive function, and depression). Data from the 2013 and 2019 Japan Gerontological Evaluation Studies were used. Healthy life expectancy was assessed using the multistate life table method. Results: Overall, 8,956 individuals were included. For both men and women, healthy life expectancy was shorter in the symptomatic group than in the asymptomatic group for several domains of the Kihon Checklist. For men, the difference between individuals with risk factors and those with no risk factors was the maximum for confinement (3.83 years) and the minimum for cognitive function (1.51 years). For women, the difference between individuals with risk factors and those with no risk factors was the maximum for frailty (4.21 years) and the minimum for cognitive function (1.67 years). Healthy life expectancy tended to be shorter when the number of risk factors was higher. Specifically, the difference between individuals with ≥3 risk factors and those with no risk factors was 4.46 years for men and 5.68 years for women. Conclusions: Healthy life expectancy was negatively associated with characteristic geriatric symptoms, with strong associations with frailty, physical functional decline, and depression. Therefore, comprehensive assessment and prevention of geriatric symptoms may increase healthy life expectancy.